O jato relativístico do objeto BL Lac AO 0235+164: estrutura e cinemática - Silva Junior, Flávio Benevenuto da (2020)
Radio interferometric images of BL Lac object AO 0235+164 show the existence of a stationary core, and a compact jet composed of multiple components. In this work, we determined the structural characteristics of these jet components (core-component distance, position angle, flux density, etc.) at the frequencies of 15 and 43 GHz using our statistical method for global optimization Cross-Entropy. The analyzed images were extracted from public databases, totalizing 41 images at 15 GHz and 134 at 43 GHz. Using criteria such as the value of the CE merit function, and mean residuals, we determined the optimum number of components in each epoch analyzed in this work. The temporal evolution of the spatial coordinates of the jet components was used to determine their speeds and ejection epochs. We identified 34 components in the jet of AO 0235+164, with apparent speeds roughly between 2,7c e 39,2c, and distributed across all four quadrants in the plane of the sky. Based on these values, the value of the Lorentz factor and the angle of orientation of the jet of AO 0235+164 in relation to the line of sight are estimated in this work.